SOCIAL MOTIVES OF HESYCHASM - Іщук, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article deals with the theo anthropology of Hesychasm in its connection with the social teaching of Orthodoxy. It is proved that sociality is not a characteristic attribute of Hesychasm and unfolds centrifugally – from the theo anthropological conception of synergy with God to the idea of moral perfection of the individual and society.